Impact of The Covid-19 Pandemic on The Effectiveness of Ship Crew Schedule at PT Surf Marine Indonesia - Putu Ayu Damayanti; Derma Watty Sihombing; Susi Herawati (Greenation Research & Yayasan Global Resarch National, 2023)
Health is very important for all humans, because without good health it will be difficult to carry out daily activities. According to the Health Law Number 36 Year 2009 Article 1